Breeding for disease resistance in farm animals - Bishop, S. C. [ (Stephen C.)] (CABI, 2010)
Addressing principles associated with breeding animals for enhanced health and resistance to specific diseases, this title presents a review of the field with examples covering many diseases of importance to livestock production across various major livstock species